Dinamika Lingkungan sebagai Moderator Pengaruh Perencanaan Strategik dan Perencanaan Operasional terhadap Kinerja Perusahaan Nirlaba (Studi pada Rumah Sakit di Kota Banjarmasin) - Rifani, Ahmad; Basuki, Ananto (Universitas Brawijaya, Indonesia, 2008)
This research was done at non-profit companies. Whereas, there was limitation number of research that connecting with non-profit company. The aim of this research were to describe non-profit strategic typology that was used by hospitals in Banjarmasin, to know environment dynamic variable as moderator in the influence of strategic planning and operational planning toward non-profit company's performance, based on balanced scorecard approach. This research was kind of explanatory research, defines as the research that explains correlation between variables and tests the hypothesis. The population is people who work in hospital and get involves in strategic planning arranger and operational planning at each hospitals in Banjarmasin. Census sampling technique was used in this research, which were resulted 60 peoples as respondent. Hypothesis was tested by Moderated Regression Analysis (MR4). The result of this research showed five in eight hospitals have been implicating non-profit strategic typology that was piggybacking strategy. Second, the result showed that the dynamical of environment is moderator in the influence of strategic planning and operational planning toward non-profit company's performance, based on balanced Scorecard approach. Third, the result of this research also showed that the dynamical of environment is moderator in the influence of strategic planning and operational planning toward non-profit company's performance, based on balanced scorecard approach, significantly.